An Analysis of Business Turnaround as a Consecutive and Concurrent Process. - Husein, Zeffirra (2008)
This paper attempts to give an overview of how loss making or dieing businesses can be turned around by means of employing various strategies and steps recommended by experts and researchers. It analyses each aspect during the process of turnaround from the ‘reasons for decline’ to the ‘final outcome’ and discerns influencing relationships between these aspects to determine whether these relationships have an impact on the resultant outcome. The influence of skipping a few recommended steps during the turnaorund process is also questioned and the impact of the step skipping is placed under scrutiny. In doing so the paper has synthesized extant literature which was employed to construct the conceptual framework, which was inturn used to analyse the cases under study. During the course of preliminary research for the study I discovered that each aspect of turnaround is studied in isolation in most of the studies. My paper has attempted to synthesize all the aspects put togeteher and apply the constructed literature to analyze thecase studies in order to discern any linkages and relationships within the aspects and between the outcome. Finally the paper recommends further research on the influence of encironmental factors on the other aspects of turnaround and the resultant outcome.